Libraries in society: comparing international metrics of societal progress to library usage statistics - Margaret Sullivan (Information Research: An International Electronic Journal)
Introduction. Literacy is a major predictor of education, income, and health. Both historically and currently, libraries have been leaders in promoting literacy globally. The objective of this research is to determine if countries with higher metrics related to the Sustainable Development Goals also demonstrate evidence of stronger relationships between library usage and literacy.